Numerical modeling of physical fields in the process of drying of paper for corrugating by the infrared radiation - Karvatskii, Anton; Marchevsky, Viсtor; Novokhat, Oleh (Eastern-European Journal of Enterprise Technologies, 2017)
By using a numerical model, developed based on the proposed physical and mathematical models, we performed a numerical study of non-stationary temperature fields and moisture content of the process of infrared radiation drying of fluting. A distinctive feature of present study is a combined consideration of the kinetics of drying process, translucency to the IR radiation of the material using the approximations of the Burgers' models, "gray" medium and diffuse reflection of boundaries. Verification of the numerical model demonstrated a convergence of results of numerical modeling of the fluting surface temperature, duration and speed of its drying with the data of physical experiment within the range of 5 % on the interval of change in the square meter mass of dry fluting from 0.112 kg/m2 to 0.2 kg/m2. It is substantiated that the developed numerical model makes it possible to define kinetic patterns and basic parameters required to intensify the process of drying and to design the appropriate equipment.